1997
DOI: 10.1183/09031936.97.10020354
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma and allergy in Hong Kong schoolchildren: an ISAAC study

Abstract: Asthma and allergic disease in children is increasing in many Western countries but such trend has not been well-defined in Chinese populations. This paper aims to determine the prevalence of asthma and allergic disease in Hong Kong schoolchildren and compare it with previous data to identify a changing trend.We studied 4,665 schoolchildren aged 13-14 yrs using the International Study of Asthma and Allergy in Childhood (ISAAC) protocol to determine prevalence rates for asthma, wheeze, respiratory symptoms, rhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
137
3
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(150 citation statements)
references
References 31 publications
6
137
3
2
Order By: Relevance
“…These findings are in accordance with studies showing a male predominance for wheezing during the first decade of life, which is reversed around the time of puberty [21,22]. In Hong Kong, higher prevalences of respiratory symptoms were found in male schoolchildren [16], but, when severe respiratory symptoms were considered, the sex difference became less obvious. Although one explanation for the observed sex difference in the severity of asthma could be a tendency of females to overestimate the severity of the disease, the fact that this is a worldwide observation supports this difference being real.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in accordance with studies showing a male predominance for wheezing during the first decade of life, which is reversed around the time of puberty [21,22]. In Hong Kong, higher prevalences of respiratory symptoms were found in male schoolchildren [16], but, when severe respiratory symptoms were considered, the sex difference became less obvious. Although one explanation for the observed sex difference in the severity of asthma could be a tendency of females to overestimate the severity of the disease, the fact that this is a worldwide observation supports this difference being real.…”
Section: Discussionsupporting
confidence: 90%
“…In Japan, advances in laboratory test methods may have changed the diagnostic criteria and increased the number of reported cases of allergic rhinitis32). However, the observed increase in asthma was not simply due to an increased awareness of asthma, reporting and labeling bias because it has been reported that the prevalence of asthma had increased anyway, even when the same diagnostic criteria were used during the study periods 12,14).…”
Section: Discussionmentioning
confidence: 88%
“…Outros estudos, utilizando uma faixa etária mais estreita, não observaram diferenças nas taxas de prevalência, em casos de chiado no peito (47) . As condições favoráveis de nascimento dessas crianças podem ter influenciado no sentido de atenuar a morbidade respiratória das menores de um ano.…”
Section: Discussionunclassified